Marine Natural Products and Coronary Artery Disease - Liang, Bo; Cai, Xin-Yi; Gu, Ning (Frontiers in Cardiovascular Medicine, 2021)
Coronary artery disease is the major cause of mortality worldwide, especially in low- and middle-income earners. To not only reduce angina symptoms and exercise-induced ischaemia but also prevent cardiovascular events, pharmacological intervention strategies, including antiplatelet drugs, anticoagulant drugs, statins and other lipid-lowering drugs, and renin-angiotensin-aldosterone system blockers, are conducted. However, the existing drugs for coronary artery disease are incomprehensive and have some adverse reactions. Thus, it is necessary to look for new drug research and development. Marine natural products have been considered a valuable source for drug discovery because of their chemical diversity and biological activities. The experiments and investigations indicated that several marine natural products, such as organic small molecules, polysaccharides, proteins, and bioactive peptides, and lipids were effective for treating coronary artery disease. Here, we particularly discussed the functions and mechanisms of active substances in coronary artery disease, including antiplatelet, anticoagulant, lipid-lowering, anti-inflammatory, and antioxidant activities.